Midpoint Results of National Surveillance of Childhood Tuberculosis. (1st June 2016) - Giroux, R; Jamal, A; Kitai, I; Consunji-Araneta, R; Baikie, M; Morris, SK
Abstract: BACKGROUND: There is little detailed epidemiologic and clinical data about tuberculosis (TB) disease in children in Canada. OBJECTIVES: To characterize the epidemiologic, clinical, and treatment data for all cases of TB in children under age 15 in Canada through the Canadian Pediatric Surveillance Program's (CPSP) Childhood Tuberculosis Study. The initial results of the 3 year study presented here includes cases from September 2013 to October 2015. DESIGN/METHODS: TB cases were identified through a monthly form sent by the CPSP to approximately 2500 active pediatricians, pediatric subspecialists, and select non-pediatricians who manage childhood TB. For cases meeting inclusion criteria, a detailed questionnaire was sent to collect clinical, epidemiological, and treatment data, followed by 6-month follow-up surveys until 6 months after treatment completion. RESULTS: Of 164 unique incident cases reported, 84 met inclusion criteria and returned a detailed questionnaire. Selected demographic data is shown here: Intrathoracic TB was reported in 78/84 (93%) of cases including 66 with pulmonary disease. One or more positive cultures were obtained in 32/68 (47%) of cases attempting pulmonary culture using sputum (n=17), bron-choalveolar lavage (n=2), and/or gastric aspirates (n=16). Of these, 4/9 (44%) were positive in children 12 months or younger, 8/23 (35%) between ages 1-4, 5/14 (36%) between ages 5-9, and 15/22 (68%) in children 10+ years. In two culture-negative cases, a positive AFB was found in the sputum. Extrathoracic TB was reported in 30% (n=25), with rates in children 10+ years being significantly higher than expected given the current literature. One case was MDR-TB. CONCLUSION: Detailed clinical, epidemiological, and treatment data has been obtained for many cases of childhood TB in Canada through the CPSP Childhood Tuberculosis Study. This study will provide the most complete picture of childhood TB in Canada and will serve to refine practice in monitoring, detecting, and treating this infection.